Reseña de libro: Making peace with faith: the challenges of religion and peacebuilding (Revista Latinoamericana Estudios de la Paz y el Conflicto, 2020)
GARRED MICHELLE, ABU-NIMER MOHAMMED (2018). Making peace with faith: the challenges of religion and peacebuilding. Lanham: Rowman & Litlefield. 264 pp.